IMPLEMENTASI KEBIJAKAN PENDIDIKAN GRATIS DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SEKOLAH MENENGAH ATAS NEGERI 1 KABUPATEN BULUKUMBA - Hermawati Mappiwali; Jusman; , Rijal (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The implementation of free education policies in improving student achievement provides benefits for improving the quality of education, especially high schools in Bulukumba Regency by increasing student participation in learning motivation supported by teaching staff and good infrastructure. The purpose of this study was to determine the implementation of free education policies in improving student achievement at State Senior High School 1 Bulukumba Regency which is supported by good facilities and infrastructure. This research uses a qualitative descriptive approach focusing on case study analysis using an interactive model. The data collection techniques used were observation, documentation and interviews. The results showed that the implementation of the free education policy in the learning process in improving student achievement in the learning process went well. It can be seen that with this policy, the learning process in improving student achievement and resources, especially teachers, is getting better. On the other hand, the procurement of facilities and infrastructure has not been maximised, this is because the allocation of free education funds in Bulukumba Regency decreases every year so that it has an impact on the learning process and student achievement and the improvement of teacher welfare looks less than optimal, especially the provision of incentives for excess teaching so that it affects student achievement in learning.